2018
DOI: 10.1155/2018/6527549
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Evaluation of the Influence of Panax ginseng on the Pharmacokinetics of Three Diester Alkaloids after Oral Administration of Aconiti Lateralis Radix in Rats Using UHPLC/QQQ‐MS/MS

Abstract: Objectives To investigate whether Panax ginseng (P. ginseng) could affect the metabolism of Diester Alkaloids (DAs) derived from Aconiti Lateralis Radix in vivo. Methods and Results 24 male Sprague-Dawley rats were randomized for 7-day treatment with P. ginseng (low, middle, and high), or vehicle. Aconiti Lateralis Radix was administered orally to each group on the 8th day. Plasma samples were collected, and Xevo TQ-S was used to detect the concentration of aconitine, mesaconitine, and hypaconitine in plasma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The results are shown in Figure 2, indicating that there is no obvious system residual with this method. Compared with other methods, the analysis time was shorter and the extraction method was simpler in our research (Ouyang et al, 2018;Yang et al, 2018).…”
Section: Selectivitymentioning
confidence: 77%
“…The results are shown in Figure 2, indicating that there is no obvious system residual with this method. Compared with other methods, the analysis time was shorter and the extraction method was simpler in our research (Ouyang et al, 2018;Yang et al, 2018).…”
Section: Selectivitymentioning
confidence: 77%
“…In our previous study, we had suggested that P. ginseng can inhibit the clearance of aconitine, mesaconitine, and hypaconitine in rats. This results in the fact that the accumulation of aconitine, mesaconitine, and hypaconitine within the body may be the basis of DDI between P. ginseng and Aconiti Lateralis Radix [33].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiment has shown that Ginseng could reduce the metabolism of DDAs through inhibition of CYP3A4 expression and activity [ 79 ]. In a rat model, Ginseng could slow down the metabolisms of DDAs from Fuzi when given orally [ 80 ]. Ginseng combines with Fuzi could increase SOD activity and reduce malondialdehyde (MDA), nitrogen oxide and lactate dehydrogenase, which could enhance cardiac cell viability [ 81 ].…”
Section: Detoxification Of Aconitum In Traditional and Modern Waysmentioning
confidence: 99%
“…In vitro experiment has shown that Ginseng could reduce the metabolism of DDAs through inhibition of CYP3A4 expression and activity [79]. In a rat model, Ginseng could slow down the metabolisms of DDAs from Fuzi when given orally [80].…”
Section: Ginsengmentioning
confidence: 99%